Challenges of Current National Reference Frame (NRF) and Map Sheet Layout in Nepal Cadastral Mapping - Rajbhandari, Sushil Narsingh; Dhakal, Damodar (Journal on Geoinformatics, Nepal, 2023)
Systematic Cadastral mapping in Nepal used to be carried out using local coordinates. Later National Reference Frame (NRF) and a map sheet layout is being used to improve the situation. Current trend of use of GNSS in establishing control points demands a set of transformation parameters. The coordinates in NRF which are obtained by transforming the GNSS results, does not give expected accuracy to be used for large scale mapping. In addition, map sheet layout is being used not in line with the guidelines due to complications at the margins of projection zones. The conclusion is the current NRF and map sheet layout is not appropriate to use further for large scale mapping – which demands improvements in reference frame as well as projection system.